Caregiving among young adults in Ireland - Helen Russell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2024)
Care is fundamental to the fabric of social relationships and a significant proportion of the adult population is engaged in regular care for children and/or adults with illnesses or disabilities. Increasing attention internationally is being paid to the role of young carers (those under 18) and young adult carers (usually 18-25 years of age). However, much of the research conducted has been cross-sectional in nature and has focused on care for those with illnesses, rather than the full spectrum of care for others. This report draws on rich data on over 4,000 young people from Cohort '98 of the Growing Up in Ireland (GUI) study to take a longitudinal perspective, documenting the profile of young adult carers at 17 and 20 years of age and exploring the implications of such caregiving for their wellbeing, relationships and educational pathways.
Keywords: 330; Junge Erwachsene; Häusliche Pflege; Irland